Repeated adenoviral administration into the biliary tract can induce repeated expression of the original gene construct in rat livers without immunosuppressive strategies. Issue 8 (9th July 2004) - Tominaga, K; Kuriyama, S; Yoshiji, H; Deguchi, A; Kita, Y; Funakoshi, F; Masaki, T; Kurokohchi, K; Uchida, N; Tsujimoto, T; Fukui, H
Abstract : Background: Systemic adenoviral readministration appears to be limited by immunogenicity. Aims: We examined the feasibility of repeated adenovirus mediated gene transfer into the liver via the biliary tract. Methods: Recombinant adenoviruses carrying a reporter lacZ gene were infused retrogradely into the common bile duct of rats. Transduction efficiency of the lacZ gene was estimated histochemically and quantitatively. Results: Retrograde administration of recombinant adenoviruses into the common bile duct of rats resulted in efficient transgene expression in the liver, specifically in hepatocytes, but not in biliary epithelia. Transduction efficiency induced by intrabiliary adenoviral administration was not substantially different from that induced by intraportal adenoviral infusion. Transgene expression in the liver was however transient, and development of neutralising antibodies against adenovirus was observed in serum but not in bile. When adenoviruses were readministered into the common bile duct, successful re-expression of the transgene in the liver was achieved despite the existence of neutralising antibodies in serum. Interestingly, although proliferation of adenovirus specific T cells in response to adenoviral readministration was suppressed significantly by immunosuppressive FK506 treatment, levels of transgene expression in the liver achieved by intrabiliary adenoviral readministration were not significantly different between animals treated with and without FK506. Furthermore, third adenoviral administration into the common bile duct also induced successful transgene expression in the liver. Conclusions: These results suggest that adenovirus mediated gene transfer into the liver may be repeatable without immunosuppressive strategies in clinical settings by means of endoscopic retrograde cholangiography.